2012
DOI: 10.1002/acr.21678
|View full text |Cite
|
Sign up to set email alerts
|

Using exercise training to counterbalance chronotropic incompetence and delayed heart rate recovery in systemic lupus erythematosus: A randomized trial

Abstract: Objective. To evaluate the efficacy of a 3-month exercise training program in counteracting the chronotropic incompetence and delayed heart rate recovery in patients with systemic lupus erythematosus (SLE). Methods. A 12-week randomized trial was conducted. Twenty-four inactive SLE patients were randomly assigned into 2 groups: trained (T; n ‫؍‬ 15, 3-month exercise program) and nontrained (NT; n ‫؍‬ 13). A sex-, body mass index-, and age-matched healthy control (C) group (n ‫؍‬ 8) also underwent the exercise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 27 publications
4
29
1
7
Order By: Relevance
“…In line with these observations, Miossi et al [79] described improvements in chronotropic responses during exercise as the result of a 3-month exercise training programme (resistance and endurance training) in patients with systemic lupus erythematosus. Keteyian et al [35] showed that exercise training for a duration of 24 weeks resulted in an increase in peak HR and HR reserve during exercise testing, as well as partial reversal of CI, in patients with heart failure.…”
Section: Exercise Therapymentioning
confidence: 78%
See 1 more Smart Citation
“…In line with these observations, Miossi et al [79] described improvements in chronotropic responses during exercise as the result of a 3-month exercise training programme (resistance and endurance training) in patients with systemic lupus erythematosus. Keteyian et al [35] showed that exercise training for a duration of 24 weeks resulted in an increase in peak HR and HR reserve during exercise testing, as well as partial reversal of CI, in patients with heart failure.…”
Section: Exercise Therapymentioning
confidence: 78%
“…Moreover, exercise training positively affects baroreceptor sensitivity and HR variability [18]. It is thus speculated that improved chronotropic responses during exercise testing, as a result of endurance exercise training, are related to increases in b-adrenergic receptor sensitivity and improved nervous system parasympathetic-sympathetic balance [18,32,35,79,80]. In addition, improvements in chronotropic responses during exercise testing seem to correlate with improvements in VO 2 peak and cardiac output [18,32,35,79,80].…”
Section: Exercise Therapymentioning
confidence: 99%
“…Unchanged or improved inflammatory markers ■ Unchanged or improved disease activity scores and markers of systemic inflammation (erythrocyte sedimentation rate and C-reactive protein) in response to aerobic, 72 Improved cardiovascular function ■ Improved endothelial function and lipid profile in response to aerobic 80 and aerobic plus resistance exercise programmes, 106 and shown by cross-sectional studies 80,103,104,106 ■ Improved autonomic function in response to aerobic plus resistance exercise programmes in in adult SLE 108 and in response to aerobic exercise programmes in juvenile-onset SLE 82,108 Unchanged or decreased levels of inflammatory markers ■ No changes in disease activity scores or markers of systemic inflammation (erythrocyte sedimentation rate and C-reactive protein) in response to aerobic plus resistance exercise in adult SLE 106,108 and to aerobic exercise programmes in adult [78][79][80][81] and juvenile-onset SLE 81 ■ Unchanged or improved levels of selected proinflammatory and anti-inflammatory cytokines and soluble receptors at rest and after exercise (IL-6, IL-10, IFN-γ, TNF, sTNFR1, sTNFR2) in response to aerobic exercise programmes 78…”
Section: Physical Capacity and Functional Improvementsmentioning
confidence: 99%
“…In addition, a randomized controlled trial study by Prado et al [22] demonstrated an increase in chronotropic response (∆ heart rate response rest-peak exercise) in childhood-SLE patients after three-month aerobic exercise training. Likewise, Miossi et al [39] showed an improvement in chronotropic reserve after an exercise training program in women with SLE.…”
Section: Exercise Training and Aerobic Capacitymentioning
confidence: 92%